2011
DOI: 10.5755/j01.erem.58.4.677
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Land in Master Plans of Towns from the Point of View of Sustainable Spatial Development

Abstract: Rational use and protection of land depend to a considerable degree on territorial planning documents, especially on municipality general plans which contain definitions of land use objective, character and type. National policy results depend on the quality of these documents. One of the most important territories planning objectives stated in the law on the Territorial Planning is: save, use rationally and restore natural resources; create healthy and harmonious environment for life, work and rest; form natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Some Western countries emphasise the importance of an individual for development (USA), but in Europe the balance between an individual and public interests is more preferable. General plans of the largest Lithuanian cities and towns as well as surrounding territories have been studied by many researchers [Bardauskienë 2007, Dringelis et al 2011, Kavaliauskas and Šabanovas 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Some Western countries emphasise the importance of an individual for development (USA), but in Europe the balance between an individual and public interests is more preferable. General plans of the largest Lithuanian cities and towns as well as surrounding territories have been studied by many researchers [Bardauskienë 2007, Dringelis et al 2011, Kavaliauskas and Šabanovas 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Since the middle of the 20 th century the territory of European urban settlements had expanded circa 78 percent on the average, while the population increase was only circa 33 percent. Currently areas of new development in cities sometimes are several times larger that the existing built-up urban areas (Dringelis et al, 2011). D. Bardauskienė and M. Pakalnis (2012) note that in Lithuania suburbanization does not correlate with a demographic and economic situation, as circa 70 percent of country's population live in expanding urban settlements, but the total number of inhabitants is shrinking.…”
Section: Introductionmentioning
confidence: 99%
“…The urban sprawl is leaving to decay the historical city centers, while assaulting the natural surroundings of cities and leaving there not only new constructions but also wastelands and waste dumps." L. Dringelis et al (2011) had identified numerous problems related with the uncoordinated urban sprawl: low residential density and lack of service infrastructure, high transportation costs, serious damage to agriculture due to the inappropriate use of fertile land, negative impact on attractive recreation facilities and tourism development prospects, ecological problems, such as urbanization of slopes, swampy areas, stream valleys etc. These problems were not left without a response.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations